2018
DOI: 10.3390/rs10101526
|View full text |Cite
|
Sign up to set email alerts
|

NPP-VIIRS DNB Daily Data in Natural Disaster Assessment: Evidence from Selected Case Studies

Abstract: Whereas monthly and annual nighttime light (NTL) composite datasets are being increasingly used to estimate socioeconomic status, use of the National Polar-orbiting Partnership Visible Infrared Imaging Radiometer Suite (NPP-VIIRS) Day/Night Band (DNB) daily data has been limited for detecting and assessing the impact of short-term disastrous events. This study explores the application of daily NPP-VIIRS DNB data in assessing the impact of three types of natural disasters: earthquakes, floods, and storms. Daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
99
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 51 publications
1
99
0
1
Order By: Relevance
“…Sensors on a satellite can capture the brightness of cities, farms, industrial areas, fishing vessel lights, forest fires, and other human activity areas at night and form a nighttime light image [6,7]. Nighttime light data can make up for the deficiency of statistical data for urban research in some respects, and can be applied to studies related to human activities due to the strong correlation between human activities and the lightmaps of population, GDP, or power consumption [8].At present, nighttime light data are widely used in research on urban expansion [9], urban morphology and structure [10,11], estimation of socioeconomic status [12][13][14][15], fisheries [16,17], and energy [18,19]. It has been found that population distributions and light intensities have significant correlations [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sensors on a satellite can capture the brightness of cities, farms, industrial areas, fishing vessel lights, forest fires, and other human activity areas at night and form a nighttime light image [6,7]. Nighttime light data can make up for the deficiency of statistical data for urban research in some respects, and can be applied to studies related to human activities due to the strong correlation between human activities and the lightmaps of population, GDP, or power consumption [8].At present, nighttime light data are widely used in research on urban expansion [9], urban morphology and structure [10,11], estimation of socioeconomic status [12][13][14][15], fisheries [16,17], and energy [18,19]. It has been found that population distributions and light intensities have significant correlations [20].…”
mentioning
confidence: 99%
“…At present, nighttime light data are widely used in research on urban expansion [9], urban morphology and structure [10,11], estimation of socioeconomic status [12][13][14][15], fisheries [16,17], and energy [18,19]. It has been found that population distributions and light intensities have significant correlations [20].…”
mentioning
confidence: 99%
“…Lower altitude (500-2000 km) orbiting satellites have finer resolution that makes it easier to detect fires in their early phases, but they take several hours to days to return to the same view. For example, VIIRS has a 12 h revisit time, together the two MODIS satellites cover the Earth four times per day, and Landsat-8 has a 16 day revisit time [16][17][18]. It is rare, but has happened, that one of these satellites provides the first notification of a fire because the fire would have to start just as the satellites happens to be passing overhead.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [38] used the National Aeronautics and Space Administration (NASA) Black Marble nighttime data (a type of high-quality NTL data from NPP-VIIRS DNB) and PNL to assess disaster-related power outages. Zhao et al [39] evaluated the power recovery after a hurricane disaster based on NPP-VIIRS images. In the Hurricane Hudhud incident, NPP-VIIRS image-based estimations of the proportion of users without power were consistent with the reported power-outage situation, showing that the NPP-VIIRS DNB daily data were effective for detecting damage and power outage caused by the storm.…”
Section: Introductionmentioning
confidence: 99%
“…In the Hurricane Hudhud incident, NPP-VIIRS image-based estimations of the proportion of users without power were consistent with the reported power-outage situation, showing that the NPP-VIIRS DNB daily data were effective for detecting damage and power outage caused by the storm. In summary, the most commonly used methods for detecting changes in NTL remote-sensing images include pixel-based image comparisons before and after events [33,35,37,39] and region-based time-series analyses [32,38].…”
Section: Introductionmentioning
confidence: 99%